2019
DOI: 10.1093/jac/dky548
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic considerations regarding the treatment of bacterial sexually transmitted infections with azithromycin: a review

Abstract: Pharmacokinetic considerations regarding the treatment of bacterial sexually transmitted infections with azithromycin-A review

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 108 publications
0
81
0
3
Order By: Relevance
“…The frequency of azithromycin and ciprofloxacin resistance in several European countries in 2015-2017 is presented in Table 5 [53, [90][91][92]. Another problem is that azithromycin can be less effective in oropharyngeal than urogenital gonococcal infections [93].…”
Section: Resistance To Macrolidesmentioning
confidence: 99%
“…The frequency of azithromycin and ciprofloxacin resistance in several European countries in 2015-2017 is presented in Table 5 [53, [90][91][92]. Another problem is that azithromycin can be less effective in oropharyngeal than urogenital gonococcal infections [93].…”
Section: Resistance To Macrolidesmentioning
confidence: 99%
“…In any circumstance, even if systemic spread of the infection is the case, the primary focus must be eliminated, and this means the antibiotic drug must be able to penetrate to the primary focus in sufficient concentrations to kill or inhibit the pathogenic bacteria – also known as ‘the drug to the bug’. In accordance, a recent review underlined the importance of the distribution of azithromycin to the anatomical site of infection or the treatment of bacterial sexually transmitted diseases .…”
Section: Focus Attainmentmentioning
confidence: 94%
“…Small studies do not differentiate between intra and extracellular concentrations, but have demonstrated significant concentrations of azithromycin in the rectum and vagina after~5 h, peaking at 24-48 h. 10,11 Tissue penetration of azithromycin is excellent, with levels up to 50-fold higher than those in serum, 9 yet it should be noted that tissue penetration may be overestimated and vulnerable to contamination by other fluids (such as blood) through sampling. 12 Azithromycin is also taken up by phagocytic cells, which deliver and release the antibiotic at the site of infection, further increasing local drug concentrations. 13 Administration of larger single doses (2 g) lead to early high levels of the drug in both serum and white cells compared with a daily dosing of 500 mg for 3 days, maximising antimicrobial concentrations early, when bacterial load is likely to be highest.…”
Section: Azithromycinmentioning
confidence: 99%